(untitled) (Scientific journal of the Fergana State University, 2024)
The purpose of the study is to determine the degree of impact on the cotton weevil of certain agrotechnical measures usually used in cotton cultivation, and to what extent they can be used against the pest. For the first time, measures for autumn plowing, salt washing and irrigation, cultivation, irrigation, mulching and defoliation were studied. Of the results obtained as a result of research and observations, the main ones were the following: